Analyses of Vegetation Used by Long-tailed Macaque (Macaca fascicularis Raffles 1821) in Tinjil Island - Dyah Perwitasari-Farajallah; Hana Intishar Sawitri; Silvy Thiyana; Tommy Langgeng Abimanyu; Entang Iskandar; Huda Shalahudin Darusman (Universitas Gadjah Mada, 2023)
Tinjil Island is a semi-natural breeding facility for long-tailed macaques (Macaca fascicularis) managed by Primate Research Center, IPB University, located at the southern of Java Island and surrounded by the Indian Ocean. Long-tailed macaques are considered frugivorous even though they are well-known for their flexible diet. This study aims to analyse the vegetation supporting the population of long-tailed macaques. Data were collected from six tracks using square sampling plots with the size of 20 m x 20 m for trees as the main plot, inside the main plot were square subplots consisting of 10 m x 10 m for poles, 5 m x 5 m for saplings, and 2 m x 2 m for seedlings. The Important Value Index (IVI) was calculated for each level of vegetation. Hanjuang (Dracaena elliptica) dominated the seedlings with 29.35%, followed by Kampis (Hernandia peltata) with 18.73%, and Kalapari (Pongamia pinnata) with 13.73%. Hanjuang (Dracaena elliptica) also dominated the saplings with 26.83%, followed by Pancal (Syzygium antisepticum) with 19.19%, and Laban (Vitex pubescens) with 12.30%. The poles were dominated by Ki Cau (Dolichandrone spathacea) as high as 59.28%, while Waru (Thespesia populnea) and Ki Ciat (Ficus septica) dominated at 40.47% and 36.15%, respectively. Kampis (Hernandia peltata) dominated the trees with 39.28%, followed by Ki Ara (Ficus glomerata) with 35.56%, and Ki Langir (Dysoxylum amooroides) with 28.70%. Species found on Tinjil Island are mostly Moraceae (9.84%) and Fabaceae (9.84%), followed by Malvaceae (8.20%), Euphorbiaceae (4.92%), Myrtaceae (4.92%), and Anacardiaceae (4.92%). The vegetation in Tinjil Island supports the livelihood of long-tailed macaques on the island because they have an abundance of food and staple food such as figs to help them fulfil the energy needed to survive and reproduce.